Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1170450696 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "TaxonKey is Animalia", "Year 1600-2020" ] } The dataset includes 1170450696 records from 16567 constituent datasets: 17 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1688 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 160 records from UWIZM Anoles. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 59 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 2276 records from Macrobenthos Chukchi Sea, 1986. 20 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 8 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 366 records from Station de Biologie des Laurentides de l'Universit? de Montr?al - Collection Ornithologique. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from An?lisis del ictioplancton del ecosistema costero de Celest?n, Yucat?n, M?xico. 15 records from Tardigrad collection of the National Museum of Nature and Science. 39 records from Faunal assemblage of sediment core TR149-31. 21 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 599 records from Distribuci?n hist?rica, prospecci?n actual y ?reas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, M?xico. 18 records from Naturtag. 17 records from donn?es esp?ces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 86 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Sch?ffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (St?l, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedici?n Seaflower 2017 proyecto Colombia BIO. 7247 records from Colec??o Entomol?gica IIA. 16687 records from MZFC/Coleccion de Aves. 1190 records from Cole?pteros presentes en un proceso de restauraci?n pasiva en bosque seco tropical. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 1068 records from DMNS Egg Collection (Arctos). 13159 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 380 records from Orthoptera - SMF. 5409 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 83803 records from Florida Keys Reef Visual Census 2014. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 2 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 744 records from Collection de longicornes et autres col?opt?res saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 340 records from Universidad del Valle de Guatemala - Colecci?n de Artr?podos. 3 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 9 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colecci?n Zool?gica Universidad del Tolima (CZUT) - Ar?cnidos. 21838 records from An?lisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos hist?ricos y ecol?gicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6126 records from Plecoptera. 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 5 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 167 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 11 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 962 records from Bees in the UVM Zadock Thompson Zoological Collection. 14 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 62109 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 19 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 116 records from BIRDRACE The early birds. 1933 records from Donn?es odonates collect?es par le CEN Aquitaine entre 1995 et 2015. 1289 records from RECORD Orthoptera Data. 10 records from Oberservation of birds at station PS14/143 along 49? West. 1747 records from Herpetofauna de la regi?n marina prioritaria Corredor Puerto Madero, Chiapas, M?xico. 2560 records from Upper Silesian Museum, Bird Observations. 1141 records from Donn?es naturalistes de Quentin ROME. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 269 records from SEWBReC Springtails and allies (South East Wales). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 58 records from Artenvielfalt auf dem Schulgel?nde. 314 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 312 records from National Museum of Natural Science. 375 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relaci?n con actividades antr?picas (amenazas) presentes en el Parque Nacional Natural Tatam? y su ?rea de influencia.. 309 records from Agencement temporel des populations et des peuplements d'invert?br?s benthiques. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 67 records from BIRDRACE Pfeifenten. 26 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 146 records from Donn?es de la naturaliste Laurence Beauchamp. 30 records from Collections ichtyologiques et herp?tologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 13525 records from Donn?es naturalistes de Bruno OGER. 15029 records from Colecci?n de mariposas del Museo de Entomolog?a de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 5 records from First record of the genus Tanaostigma (Hymenoptera? Chalcidoidea? Tanaostigmatidae) from the Afrotropical region with description of three new species. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 436 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 82 records from Donn?es du/de la naturaliste Swoszowski Florie provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 6186 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Ar?cnidos - Miri?podos de la expedici?n al R?o Apaporis - Proyecto Colombia BIO. 33 records from Pollen profile ADR353. 57913 records from Fichier communal des ongul?s. 6 records from S?chsische Schweiz (Pfaffenstein). 576 records from Conservaci?n de la tortuga caguama del Pac?fico (Caretta caretta): protecci?n dentro del h?bitat cr?tico de alimentaci?n y desarrollo en Baja California Sur. 6 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 14 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 4289 records from R?seau de surveillance Polynesia Mana - Peuplements de poissons. 37 records from Living Cirripedia. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 23 records from Abundance of benthos infauna at station GIK23042-2. 5 records from Streuobstwiese. 442007 records from Western Australian Museum provider for OZCAM. 419 records from Colecci?n de mam?feros voladores y no voladores de la Universidad de Nari?o. 42 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 760 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paran? basin in Brazil. 79755 records from NRW Regional Data: South East Wales Non-sensitive species. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 1285 records from Suivi des aires marines prot?g?es de Moorea - Invert?br?s benthiques. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 3 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 2 records from Analyses of the recent components of sediment core PS1277-1. 8 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 46 records from Waldst?ck Bremerhagen LK Bio Kl. 12. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 15 records from Inventaire des mammif?res du Parc de la Haute-?le (93). 235 records from Estimaci?n de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 30 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 9 records from Range table from benthic foraminifers in ODP Hole 146-889A. 137 records from Bannwald Burghauser Forst. 192 records from Bulletin du Mus?um d'Histoire Naturelle [1895- ]. 25473 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Donn?es 2016 P?lobate brun Comit? D?partemental de Protection de la Nature et de l'Environnement. 2 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2125 records from ZUEC-OPH - Cole??o de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 77 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 15037 records from University of Guam Insect Collection. 28 records from Artenvielfalt des "Gr?nen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 605 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1056 records from UWIZM Molluscs. 4007 records from MCP-Aves - Cole??o de Aves. 12 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 100 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 776 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2906 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 1818 records from Inventario de flora, avifauna, mam?feros, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedici?n cient?fica en la ventana Mesay en el sector sur del Parque Nacional Natural Serran?a de Chiribiquete. 42 records from Inventaire des Octocoralliaires des fonds s?dimentaires de la r?gion ni?oise. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris ?ur?i?. 21 records from Waldst?ck am Schullandheim Bad Bederkesa. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 334 records from Aves de la expedici?n en el p?ramo de Bijagual, Boyac? - Proyecto Boyac? BIO. 1461 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Donn?es naturalistes d'Olivier DELZONS. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 168 records from BIRDRACE Bon(n)apartem?wen. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 28 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of ? tridenticulati ? and ? bidenticulati ? groups from Brazilian Amazon. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 21 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 199562 records from University of Minnesota Insect Collection. 270437 records from ARABEL - Arachnologia Belgica. 124526 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 215 records from Heinersdorfer Sumpfwiese. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 22176 records from Arctic Species Trend Index (ASTI) : Marine. 7 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 33409 records from Wolli Creek Preservation Society Bird Survey. 60940 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 11 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 30 records from Naturschutzgebiet M?chelholz (M?cheln). 31 records from Wiese am Waldrand (Gurtweil). 5 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 1519 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 113 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 147049 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 380 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 248 records from Atlas des Hym?nopt?res Pompilidae du Massif armoricain et des d?partements voisins : prospections 2018. 882 records from Midden-Limburg Fish Ponds Survey. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mam?feros de los bosques montanos del Oriente Antioque?o, Ca??n del r?o Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 895 records from Geometridae de France m?tropolitaine. 17 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 4185 records from Leicestershire and Rutland Aculeate Records. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 16618 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 205279 records from First Bird Atlas. 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 656 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from Reptilia ZMK. 1290 records from Diversity of Spiders from Azorean Trails. 70 records from Ensemble des donn?es Orthopt?res. 4170 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 90 records from Natura 2000 Vall?e de la Seille. 10136 records from Inventario de Hymen?ptera; paras?tica en M?xico. 8561 records from Colecci?n de insectos agr?colas del proyecto diversidad en sistemas de cultivos. 792 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 709 records from Museu Valenci? d?Hist?ria Natural - Fundaci?n Entomol?gica Torres Sala: FETS. 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 1533 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 74 records from BIRDRACE Nachtigallen. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Donn?es de Midi-Pyr?n?es transmises par Pascal Peyrache.. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 13 records from Donn?es naturalistes de TH?VENOT Jessica. 155 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, M?xico. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 11 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 456 records from Lucanidae. 27268 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribuci?n de la Nutria (Lontra longicaudis) en la cuenca baja del r?o Sin? en el departamento de C?rdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 70 records from Birds Specimens of Akita Prefectural Museum. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 19 records from Donn?es naturalistes de LE GLOANEC Vincent. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 32 records from MSUM Ichthyology and Herpetology Collections. 7122 records from Whale catches in the Southern Ocean. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 18271 records from River Biologists' Database (EPA). 230 records from Biometr?a peces Parque Nacional Natural La Paya. 3 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 94763 records from Tiroler Landesmuseum Ferdinandeum. 69 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 13828 records from Donn?es faune Nature 18 - 2017. 100 records from BIRDRACE Die Vriesischen Feigen-V?gel (VFV). 8851 records from Odonata records from RSPB Reserves 1970-2009. 854 records from Donn?es suppl?mentaires Atlas des Mammif?res marins. 53 records from Donn?es du/de la naturaliste Dubois Yves provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro J?nano. 26 records from Donn?es esp?ces - Expertise IPE 79. 1576739 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 37 records from Roter Berg Werdau (Leubnitz). 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 2 records from Modelaje de la distribuci?n potencial de 10 especies de anfibios y reptiles en riesgo de extinci?n con escasos registros de presencia (PLECHA). 3753 records from Donn?es naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 24733 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 76 records from Donn?es du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 62896 records from Entomology Collection at the Natural History Museum of Utah. 1 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 40 records from makran-chabahar-arthropods. 110 records from BIRDRACE LiLaLau. 72402 records from Fish specimens of Kagoshima University Museum. 3814 records from UTEP Invertebrates (Arctos). 104 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leit?o, 1929 (Araneae, Thomisidae). 26 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 10 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 140 records from Foto trampeo al interior de las ?reas del Banco de H?bitat del Meta de Terrasos. 14 records from MGYS00005313. 22052 records from CNIN/Abejas de M?xico/Apoidea. 4 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 3510 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des donn?es Odonates. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 1973 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2194 records from Modelos predictivos de distribuci?n geogr?fica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 1422 records from Donn?es du/de la naturaliste Chevreau David provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art?n Vielfalt im Kinderwald. 47 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservaci?n Guanacaste, Costa Rica. 50 records from Herpetofauna de la expedici?n Pisba - Proyecto Boyac? BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 215 records from Invasive Non-Native Species, Outer Hebrides. 18 records from Phase 2 Lowland Grassland Survey of Wales. 1541 records from Naturalis Biodiversity Center (NL) - Crustacea. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79? N section). 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 1145 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 972957 records from CLICNAT Base de donn?es naturaliste picarde g?r?e par Picardie Nature. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 413272 records from DATAVES. 23 records from Herpetofauna asociada a la cuenca del r?o Quito - Choc?, 2014. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 8555 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1475 records from The Broward College Insect Collection. 742 records from Composici?n y estructura de la ornitofauna de la reserva de la bi?sfera Pantanos de Centla. 9577 records from Ecosph?re_2017_12_18. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 68368 records from Actualizaci?n y enriquecimiento de las bases de datos del proyecto de evaluaci?n y an?lisis geogr?fico de la diversidad faun?stica de Chiapas. 58 records from Isle of Wight non-native invasive species. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajar?-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 78 records from Donn?es de la naturaliste Anna Even. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 59 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avan?ats de Blanes, Macroinvertebrados Limno. 5 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 45028 records from Syst?me d?Information R?gional sur la Faune et la Flore - FNE Centre-Val de Loire - Donn?es 2016. 128 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2642 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 269 records from South American Antarctic Marine Biodiversity Literature. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from M?tropole_Nice_C?te_d'Azur_2017_12_18. 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 22 records from Ostracoda abundance of Hole 24-238. 1923 records from Donn?es de la naturaliste Lemoine Delphine provenant de la base de donn?e du SINP ?le-de-France CETTIA. 575 records from Modelaci?n de la distribuci?n y abundancia de las subespecies de venado cola blanca en M?xico: implicaciones de conservaci?n y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 111 records from Collection Hydrozoa - ZSM M?nchen. 2814 records from The reptiles and amphibians collection (RA) of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9052 records from NE Scotland other invertebrate records 1800-2010. 25 records from Base de donn?es en ligne d'observations naturalistes de mammif?res marins. GEPOG & LPO. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, M?xico: New species, new geographical records, and checklist. 42 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Donn?es opportunistes sur les odonates. 122 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 14896 records from Donn?es Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 284 records from Donn?es du/de la naturaliste Cousin Richard provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 48 records from ZUEC-ECH - Cole??o de Echinoidea do Museu de Zoologia da UNICAMP. 1381 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis H?bner (Lepidoptera: Tortricidae). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 314 records from EDIT - ATBI in Gemer area (Slovakia). 21773 records from Global compendium of Aedes albopictus occurrence. 315 records from Inventaire malacologique de la RNR des Marais de Stors. 596 records from Colecci?n de Herpetolog?a de la Universidad del Quind?o (HERPETOS-UQ). 39 records from Teich Berlin Wuhlheide. 48 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 17 records from AKG-Gel?nde (Bensheim). 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 4591 records from Respaldo de las colecciones de tejidos del Museo de Zoolog?a, Departamento de Biolog?a Evolutiva, Facultad de Ciencias, UNAM (Aves). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 77 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 84 records from Ostracoda abundance of Hole 48-403. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 1118 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 10697 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2714 records from Donn?es de la R?serve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donn?e du SINP ?le-de-France CETTIA. 19617 records from Colecci?n de Peces del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P). 35 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 92 records from Caddisflies (Insecta: Trichoptera) from Maranh?o State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 31 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 48 records from Lebensraum Gesamtschule (Langerwehe). 13 records from Foraminifera abundance of Hole 64-481. 5 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 1 records from SP-Algae - Herb?rio do Estado "Maria Eneyda P. Kaufmann Fidalgo - Cole??o de Algas. 684 records from Col?opt?res Silphid?s du d?partement du Loiret. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 390480 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammif?res marins Guadeloupe Antilles fran?aises (AET). Suppl?ments. 118 records from Observation des insectes sur le territoire de la M?tropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 3 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 177 records from Tejidos colectados en la caracterizaci?n bi?tica para la conservaci?n de especies amenazadas en el ?rea de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 16 records from Hazel Dormouse in Ireland. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 946 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 48407 records from Insects, Outer Hebrides. 33 records from An der Ohm, (Wettsaasen). 185 records from Inventaire des odonates d'int?r?t communautaire. 149 records from Restauraci?n de flora y repoblamiento de fauna nativa en 1,000 hect?reas para el restablecimiento del corredor biol?gico costero en la Laguna Madre, Tamaulipas. 10 records from Nannofossil abundance of Hole 73-521A. 1889 records from Donn?es de la collection de Hubert Piguet - Famille des Elateridae. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 3 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 2 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16745 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 6761 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 1 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 2763 records from Marine Turtles. 610 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlav?? (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 5 records from The species of the bee genus Centris of the ? hyptidis group ? revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 370 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 8 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 4 records from Nannofossil abundance of Hole 67-499B. 3927 records from Inventario y cat?logo de ostr?codos recientes de los mares mexicanos. 9 records from Jeu de donn?es convention FEGVE-SPN (num?ro 2). 2 records from S?chsische Schweiz (Wehlener Gebiet). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 66 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 6042 records from Arthur Chapman Observations. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 300 records from Cuxhavener K?stenheiden. 1433379 records from Hatikka Observation Database. 2458 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 337 records from Donn?es naturalistes de Monsieur JOURDE R?mi. 118570 records from inatura - Erlebnis Naturschau Dornbirn. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paran? basin, Brazil. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 1762 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlay?a, en Tepex? de Rodr?guez, Puebla: Fase II. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Mart?nez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 238 records from Donn?es Mammif?res marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1224 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 749 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dageb?ll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9073 records from WTSWW Data: All Taxa (West Wales). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 370 records from Fichas diagn?sticas para 10 especies de anfibios y reptiles mexicanos. 428 records from Cartograf?a de vegetaci?n a escala de detalle 1:10.000 de la masa forestal de Andaluc?a. 52 records from "Ahrschleife bei Altenahr". 301259 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 47 records from Unter hellen Zinnen und finsteren Grotten. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 96 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 2341 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 1264 records from Grand Voyeux - Suivis scientifiques. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 77 records from UWIZM Cnidarians. 299 records from Colecci?n Taxon?mica Nacional de Insectos ?Luis Mar?a Murillo? (CTNI). 78 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 24005 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 171521 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 5 records from Neotropical Chvalaea Papp & F?ldv?ri (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 1232 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 38 records from Colecci?n Ornitol?gica Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 92562 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 30 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 1249 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Troms?. 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 49 records from Faunal assemblage of sediment core TR149-32. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1865 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium M?ller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 80 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 13 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 30 records from Schulgel?nde Lise Meitner Realschule (Paderborn). 107 records from Birdrace-Uhulogen-Lippe. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Gl?er, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 131 records from Birdrace-SpeedBirder-Zwickauer_Land. 79 records from Birdrace-Die_Vogelscheuchen-Herford. 26 records from Four new species of Plega Nav?s, 1928 (Neuroptera: Mantispidae) from Mexico. 370 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 249 records from Donn?es opportunistes produites par Alexandre RUFFONI dans le cadre de l??laboration d?un guide de d?termination des larves de pl?copt?res. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 129651 records from Suivi Temporel des Rhopaloc?res de France (STERF). 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 15 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 3 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 10 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 27 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 9632 records from CSIRO, fish surveys by the Soela, 1980s. 295 records from Donn?es de VINCENT Alexis (SAPROX). 1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 50 records from Donn?es de la structure For?ts en Aulnoye provenant de la base de donn?e du SINP ?le-de-France CETTIA. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 2782 records from USAC Mammals Collection. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3160 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 250 records from Inventaire et regroupement de donn?es Natura 2000. 12699 records from Donn?es bibliographiques et opportunistes Mammif?res du Nord Pas-de-Calais issues du SIRF. 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4968 records from Moluscos de la Colecci?n de Referencia de Biolog?a Marina de la Universidad del Valle (CRM-UV). 56 records from Donn?es du/de la naturaliste Goncalves Cristina provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 24880 records from Donn?es Mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 1. 168 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Analyses of the recent components of sediment core PS1011-1. 50742 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 22 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 15 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 1123 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 29 records from MVZ Herp Observations (Arctos). 23 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 153 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 956 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 143 (N.S) n? 36 (1), 2008 - Donn?es faune. 240 records from Donn?es naturalistes d'Olivier LAURENT. 2147 records from Restauraci?n y conservaci?n de Isla Guadalupe. 13 records from Cole??o de Coleoptera da Universidade de Bras?lia. 5044 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 22 records from Site Condition Monitoring of dragonflies on Loch a? Mhuilinn SSSI potential extension - 2016. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Br?cke / B1. 6 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from C?digo de barras de ejemplares de la Colecci?n Nacional de Mam?feros del Instituto de Biolog?a, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 202114 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 109 records from BIRDRACE Die Wendeh?lse. 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 8332 records from Scotland Otter Survey Database. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1188 records from Herpetofauna de la regi?n del Mar Muerto, Oaxaca-Chiapas. 36 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 83299 records from CAS Entomology (ENT). 144458 records from Carnet B Lorraine. 5144 records from Naturalis Biodiversity Center (NL) - Pisces. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 5 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 61606 records from Donn?es du/de la naturaliste Bottinelli Julien provenant de la base de donn?e du SINP ?le-de-France CETTIA. 310068 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 38 records from Tejidos de la expedici?n en el p?ramo de Rabanal, Boyac? - Proyecto Boyac? BIO. 1045 records from Collection Trichoptera - SMF. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 92 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 11 records from Nannofossil abundance of Hole 1-3. 131 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 10 records from Nannofossil abundance of Hole 6-55. 101 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 122383 records from Arizona State University Hasbrouck Insect Collection. 63364 records from CCAMLR historic KRILL. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaun?stico de los humedales de Puerto Morelos, Quintana Roo. 3352 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetol?gica Chetumal). 119 records from Birdrace-Die_Ackerm?nnchen-Schalm-Eder-Kreis. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 177 records from Chironomid remains in the sediment sequence of Site PG1212. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 457 records from Helmintos par?sitos de peces dulceacu?colas de cuencas hidrol?gicas del Centro-Norte de M?xico (Durango). 87546 records from MDFRC macroinvertebrate survey. 177 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 16 records from Amtsrain Apolda-Zottelstedt. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 128 records from Inventaire des reptiles 2014. 457 records from MoJ BioBlitz August 2018. 53 records from Diversidad y din?mica del fitoplancton marino en la bah?a de Acapulco, Guerrero. 36 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 45 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 38 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bou?ek. 61 records from Shrews of Poland. 1 records from Nannofossil abundance of Hole 2-11. 5996 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 90 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 3 records from Nannofossil abundance of Hole 6-48B. 31 records from STELI 2015 Saint-P?e-sur-Nivelle (64) par l'association EcoGIS. 181199 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 172 records from Donn?es du/de la naturaliste Roquinarc'h Oc?ane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1267 records from Inventaire des Crustac?s D?capodes de France m?tropolitaine. Donn?es du compte CardObs 1113. 6756 records from Donn?es du naturaliste MIGUET Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 16 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 4 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 509 records from BUND - Dassower See (L?beck/Dassow). 58348 records from Donn?es naturalistes de Monsieur Fran?ois FOURNIER. 63 records from Birds and plant species near Petushki town (Vladimir region). 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 108456 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gew?sseruntersuchung (Prien) mit Kl. 4b. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 2 records from SWECO. 3760 records from Donn?es naturalistes de Lo?c SALAUN. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 34 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1939 records from East Ayrshire Species Database. 100 records from Euroants. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1519 records from Leif Richardson Vermont Bee Specimens. 11 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur ? ventre jaune - ?tude de r?partition. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 3902 records from Collection Crustacea - ZMB. 644 records from Estudio herpetofaun?stico de la Sierra Mazateca, Oaxaca, M?xico. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 12 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 14652 records from The national database for marine data (MADS). 8 records from Foraminifera abundance of Hole 57-440A. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 6 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 5 records from Warnowufer Gro? Klein. 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 45 records from Tejidos de los ejemplares colectados en la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 16611 records from Sistem?tica e historia natural de algunos anfibios y reptiles de M?xico. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en M?xico. 237 records from Evaluaci?n del ?mbito hogare?o y calidad de h?bitat del borrego cimarr?n (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Bi?sfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 21 records from Pollen data of trap CB4. 10 records from Valentin Moser Bats. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 15 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 128 records from Extracellular DNA marine sediment Targeted Locus (Loci). 25 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 60 records from "Schwarzwassertal" bei Pobershau. 1 records from marine metagenome Targeted Locus (Loci). 24468 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Koll?sen in Norway. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 134201 records from Donn?es acquises dans le cadre de l'activit? du bureau d'?tude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 87 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 541 records from Danielsberg (M?lltal, K?rnten). 90 records from Vegetaci?n vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedici?n Seaflower 2016 - Proyecto Colombia BIO. 12996 records from LPO_PACA_2017_12_18. 1 records from Nannofossil abundance of Hole 39-353A. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 118 records from Targeting a portion of central European spider diversity for permanent preservation. 574 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 46 records from Nannofossil abundance of Hole 3-15. 2057 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 88 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6468 records from Computarizaci?n de la Colecci?n de mam?feros del Centro de Investigaciones Biol?gicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 1490 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 294 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 10546 records from Collection Pisces SMF. 475 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 31450 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 27 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 4 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 1 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 65 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 201 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 146 (N.S) n? 39 (4), 2011 - Donn?es faune. 9 records from Bachpatenschaft Beeke. 461 records from Donn?es du/de la naturaliste Dodelin Beno?t provenant de la base de donn?e du SINP ?le-de-France CETTIA. 14214 records from Estado actual, identificaci?n de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrol?gicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del r?o de La Laja. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 15 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 91 records from Artenvielfalt auf den Elbwiesen (Dessau). 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 4167 records from CASES2003_2004. 31 records from Registros de mam?feros de los Parques Ecol?gicos Distritales de Monta?a de Bogot?, D.C.. 36526 records from Fife Nature Records Centre combined dataset. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibd? - Choc?, 2019. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 35 records from Naturschutzgebiet Lochbusch-K?nigswiesen. 821 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata?historical collection of the MUSE (Trento, Italy). 18 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 267 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 175 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 34 records from Naturgrundst?ck (Eutin). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 229 records from donn?es araneologiques de LEENKNEGT Virginie. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 46 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 52625 records from Donn?es de l'Observatoire de la Faune de Bourgogne. 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 4117 records from Colecci?n Herpetol?gica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 4 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribuci?n al conocimiento taxon?mico de los peces que habitan los sistemas acu?ticos de la reserva de Calakmul, Campeche. 539 records from Phenological Center - Birds (Murmansk). 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 195 records from Museu de Ci?ncies Naturals de Barcelona: MCNB-Tissue. 288 records from Echinoderms from the Seaflower Biosphere Reserve. 2 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 1 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 22 records from Review of Lepidocyrtinus B?rner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 2312 records from Donn?es naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 788 records from Fauna de cole?pteros lamelicornios del Estado de Michoac?n. Primera Fase: Subprovincia neovolc?nica tarasca (Cuenca del Lago de P?tzcuaro) 1995-96. 1173 records from Donn?es de collection de l'inventaire des Papillons de jour de Martinique. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3320 records from BioGIS - Mammals - SPNI. 19 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Direcci?n General de Medio Natural y Pol?tica Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 25851 records from Inventaire et suivis d'esp?ces dans le Parc national des C?vennes. 933265 records from SEWBReC Birds (South East Wales). 1334 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 807 records from ?rea Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 255 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5017 records from Colecci?n Entomol?gica del Programa de Biolog?a - Universidad de Caldas (CEBUC). 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 56 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 34960 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 625 records from Donn?es araign?es de Corse par Canard A., Rollard C., Villepoux O.. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6301 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 83 records from Heavy minerals of sediment core PL94-64. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 101787 records from Amphibiens et Reptiles de France (Enqu?te 2). 2095 records from Dolichopodidae of Portugal - dataset 2009-2018. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crust?ceos, equinodermos y peces) del Santuario Islas e Islotes de Bah?a Chamela, Jalisco, M?xico. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2841 records from Donn?es naturalistes d'Alain BERLY. 26966 records from Insect Collection from the Museu Nacional de Hist?ria Natural e da Ci?ncia, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 700 records from Donn?es opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 368 records from Ring ouzel national sample survey in the UK in 1999. 6710 records from Odonata de Veracruz. 264 records from BIRDRACE Niederlausitz-Team. 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 5 records from Planktic foraminifera abundance of Hole 18-173. 159 records from L?nea base del medio bi?tico en los bosques dentro de la zona propuesta para Acuerdos de Conservaci?n Voluntaria en la microcuenca de la Quebrada Aguazula - Rinc?n del Soldado_Yopal. 6639 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 364 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 374 records from CG04_2017_12_18. 717 records from Donn?es du/de la naturaliste CUENIN Sibylle provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 248 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 520 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 146 (N.S) n? 39 (1), 2011 - Donn?es faune. 22 records from Microzooplankton abundance and biomass at station TT045_15-2. 10215 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 228 records from FBIP: Identification of polychaetes used as bait. 96300 records from Denver Museum of Nature & Science - Entomology. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 14503 records from Fish Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 13 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ? notoides? clade to a new genus, Xipholeptos n. gen.. 60 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1334 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1066 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 8311 records from ??????????. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 115 records from Strathclyde badger sett surveys 1996-2000. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapaj?s basin, Brazil. 190275 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 1928 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 1 records from Nannofossil abundance of Hole 58-442B. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 38612 records from National Biodiversity Data Bank. Observation records, 1900-2014. 326 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 588 records from Occurrence database of bryophytes and native animals of southern Chile. 4 records from VFD-H: Heidenrod: Pferdeweide M?rth. 12380 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San crist?bal). 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 69 records from Nottekanal, Klasse 7 - 10. 50 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 2863 records from Inventaire des Mollusques Sphaeriidae de France. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 16885 records from donn?es aran?ologiques de CORNIC Jean-Fran?ois. 85 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 15 records from Donn?es esp?ces - Expertise IPE 69. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3838 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geogr?fico y el nicho ecol?gico en los procesos de divergencia evolutiva.. 15 records from Flora und Fauna im Brexbachtal. 652 records from Insectos asociados a cultivos de Albahaca y Aj? en Santa Marta. 3889 records from MICROBIS database. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 118 records from Birdrace-Professorenteam-M?nster. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 3238 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos las Hermosas y Chil?-Barrag?n.. 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 3066 records from Colecci?n de Mam?feros del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 485665 records from Swiss National Orthoptera Databank. 72142 records from The Environmental Sample Collection of Spiders at the Staatliches Museum f?r Naturkunde Karlsruhe. 5 records from Pollen profile II/B at Krumbach, Germany. 16730 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 229 records from Caracterizaci?n hidrogeol?gica para el diagn?stico ambiental de alternativas del proyecto hidroel?ctrico San Bartolom? (ISAGEN y HMV).. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 6 records from Nationalpark Harz Schul-AG Braunlage. 12630 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 594 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 4 records from NEW-1. 137 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaiz? et des Oiseaux de Dan Saga. 1 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 37 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimar?es & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 17 records from Biodiversity Surveys, South-east Arnhem Land. 552 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 144 (N.S) n? 37 (2), 2009 - Donn?es faune. 120 records from Tejidos asociados al estado de conservaci?n y riesgo de extinci?n del ensamblaje de anfibios de tres p?ramos colombianos. 33 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colecci?n de Peces Dulceacu?colas of Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 82 records from Donn?es naturalistes de Pierre-Alexis RAULT. 222076 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 2 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 262 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 4 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 2 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 54 records from Anfibios y reptiles de la serran?a las Quinchas, Boyac? - Proyecto Boyac? BIO. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 22 records from Ahuyentamiento, rescate y reubicaci?n de fauna en el ?rea de influencia directa del proyecto Hidroel?ctrico Mulatos II. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 53 records from Cole??o de Nematoda do Museu Nacional - UFRJ. 2 records from Description of a new species of deep-sea spider crab from the genus Crocydocinus Lee, Richer de Forges & Ng, 2019, from the south-eastern Arabian Sea (Crustacea Decapoda: Majoidea: Epialtidae). 1 records from Inventory of plant species through Benin (West Africa). 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 12088 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 70 records from Pollen record of sediment core Bokanjacko Blato 1. 6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 36 records from BIOMEO_2017_12_18. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 1 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 174 records from Bosque Mes?filo de Monta?a de M?xico. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 1009 records from Donn?es naturalistes de Daniel PAVON. 293 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 15 records from Modelaje de la distribuci?n potencial de 10 especies de anfibios y reptiles en riesgo de extinci?n con escasos registros de presencia (ANONAU). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 2 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 60 records from Caracterizaci?n de la fauna reptiliana asociada a la cuenca del r?o Atrato, para el estudio de su navegabilidad, Quibd? - Choc?, 2012. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 261103 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leit?o, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 3 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 10909 records from NCSM Mammals Collection. 27 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 23 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 91477 records from Colecci?n de Entomolog?a del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-E). 165526 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1967 records from Fototrampeo de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 425 records from Collection ornithologique A. Ma?s. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 5300 records from Actualizaci?n de la base de datos de diversidad taxon?mica de las larvas de peces de Bah?a Vizca?no. 36 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 17 records from ?rtzem?ndung (Stedden). 46509 records from National Stag Beetle Surveys (Great Stag Hunts). 51 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 86237 records from Marine Offshore Seabed Survey data held by JNCC. 3 records from Morphological and molecular evidence for a new species of the genus Panolis H?bner, [1821] (Lepidoptera: Noctuidae). 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 310 records from Donn?es naturalistes de Monsieur LEFEBVRE Fran?ois. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1211 records from Donn?es du naturaliste Marquet Jacques provenant de la base de donn?e du SINP ?le-de-France CETTIA. 11494 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Entomologica). 12 records from Mam?feros del municipio de Santa B?rbara, Santander - Proyecto Santander BIO. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O?Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 1004 records from Donn?es odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 13 records from Planktic foraminifera abundance of Hole 7-64. 1 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 41 records from Pollen profile from Seminary School Basin. 16 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 304 records from BIRDRACE G?tkes Erben. 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3249 records from Benthos counted on dredged samples during Valdivia cruise VA53. 13 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 124 records from The cryptogamy collection (PC) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 75 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 159 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 794 records from Carabidae of the European North-East of Russia. 5052 records from Actualizaci?n y depuraci?n de las bases de datos de la Colecci?n Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammif?res marins Guadeloupe Antilles fran?aises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidaci?n de la colecci?n de referencia de peces de la Estaci?n Mazatl?n, (ICMyL-UNAM) e implementaci?n de los mecanismos para su manejo y consulta. 12 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaur?s en pierre s?che en lien avec l'association "une pierre sur l'autre". 1040 records from Donn?es de l'Association naturaliste d'?tude et de protection des ?cosyst?mes CAUDALIS 2015 Chiropt?res, Maculinea, Cistude d'Europe. 1 records from Donn?es naturalistes d'Ana?s MAS. 37 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 3 records from The Myriapoda & Onychophora collection (MY) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 65 records from Donn?es du/de la naturaliste Thibault Marie Th?r?se provenant de la base de donn?e du SINP ?le-de-France CETTIA. 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 21385 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2842040 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 14 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 5 records from Two new species of Brueelia K?ler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterizaci?n Ecol?gica de la Fauna del P?ramo de Frontino o del Sol. 25 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 1 records from Sediment metagenome. 177987 records from BioFokus. 13708 records from Anymals+plants - Citizen Science Data. 17744 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 991 records from Donn?es du/de la naturaliste CARON Julien provenant de la base de donn?e du SINP ?le-de-France CETTIA. 793 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 3 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mam?feros peque?os en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 17 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 156 records from Biodiversidad de los Ecosistemas Mesof?ticos de la Isla de San Andr?s. 15446 records from Occurrences de vecteurs de maladies recens?es ? l'H?pital de M?nontin. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 376 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 5 records from Two new nematode species of the genus Tobrilus Andr?ssy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 13 records from Type locality records of Polycystididae species in the world. 8 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1088 records from Donn?es naturalistes de St?phane ORIO. 153 records from Collection Echinodermata - ZMB. 27 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 276 records from Aunar esfuerzos y recursos t?cnicos, econ?micos y humanos con el fin de adelantar acciones de investigaci?n para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 3 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del ca?o Teracay en el r?o Tomo, Puerto Carre?o, Vichada - Proyecto Colombia Bio. 17 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 532 records from Super?rden Dictyoptera del Museo de Entomolog?a de la Universidad del Valle (Cali, Colombia). 1 records from Cladistic analysis and synopsis of Chloropepla St?l (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 17 records from Comunidad de Herpetos presentes en el r?o Tutunendo, Municipio de Quibd?-Choc?. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 17 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 483 records from Donn?es du/de la naturaliste Hasrouni Sami provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 217 records from Inventaire des odonates 2014. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 24 records from Abundance of benthos infauna at station PS1240-1. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 110 records from Donn?es du R?le gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 733 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 650 records from Insectivorous Bats of Gunung Mulu National Park, Malaysia. 688 records from donn?es arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 6 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 2 records from Nannofossil abundance of Hole 3-22. 477 records from Cole??o de Ictiologia do Museu de Ci?ncias Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 5194 records from Donn?es L?pidopt?res de l'Auvergne transmises par Pascal Peyrache.. 187 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 105 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 130 records from BIRDRACE Griffin Wood Warblers. 83 records from Donn?es esp?ces -expertise IQE 3. 154 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 10 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 5 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 34 records from Range table from benthic foraminifers in ODP Hole 154-929A. 4 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 360 records from Donn?es du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 60542 records from Derek Lott Coleoptera Dataset. 2 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt des PYRENEES-ORIENTALES (66). 6 records from JCT AVH data. 1 records from University of Tennessee Bryophyte Herbarium. 6263 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 6540 records from Likona Invertebrates. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 2374 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 433 records from Amphibiens de Guyane. 18 records from Nannofossil abundance of Hole 7-62A. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 8 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 7248 records from DBRC Hemiptera species records 1969 to 2015. 5 records from BB-Biodiversit?t a. 4 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acu?ticas nidificantes de la Comunidad Aut?noma del Pa?s Vasco. 48663 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3483 records from Dorset SW Pilot species dataset. 8 records from A new large-bodied, rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) allied to Cnemaspis heteropholis Bauer, 2002 from the Central Western Ghats of Karnataka, India. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 154 records from Donn?es de la structure Philofauna provenant de la base de donn?e du SINP ?le-de-France CETTIA. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 9898 records from Cumbria Non Native Invasive Species. 35 records from Inventaire et suivi de la faune ?cras?e. 16 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 1000 records from nsmk_mm_2019. 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 78 records from Rund um den Eichwald,Schulhof Friedrich Fr?bel Gymnasium- Bad Blankenburg. 2 records from DAR AVH data. 145283 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 1 records from Nannofossil abundance of Hole 3-18. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 222 records from L??valuation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation ? sangaredi, Bok? (CESP2016-022). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 1564 records from DBL_Life. 3317 records from Reef Check in Taiwan ???????. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 835 records from Colecci?n Ornitol?gica de la Universidad Tecnol?gica del Choc?. 195 records from Pedestrian mammals census in W National Park. 1178 records from Oc?anopolis mammif?res marins en Bretagne 1993-2015. 1 records from New morphological information on Simulium wygodzinskyorum Coscar?n & Py-Daniel, 1989 (Diptera: Simuliidae). 78 records from Gronau - auf der Suche nach dem Neunauge. 910 records from Programme national de science participative sur la Biodiversit? Littorale (BioLit). 19742 records from Eden Arthropod Azores Database. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 12 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2070 records from Thrips (Thysanoptera) in Norway. 68 records from Entdeckertour am Muldestausee 1/05. 103 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulid?es d'Europe. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 103 records from BIRDRACE Diesmal sehen wir mehr. 4 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 1345 records from Weevils of Poland. 17 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1763 records from Arachnida of Costa Rica (INBio). 674 records from Donn?es du naturaliste RADOGEWSKI Alain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3061 records from Ross A. Layberry, Collection. 23 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 72 records from Birdrace_G?tkes_Schergen-Helgoland. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 8 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de C?rdoba. 44036 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 1 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 164 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt du CHER (18). 42 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 342 records from El c?digo de barras de las especies NOM-059 de mam?feros del Noroeste de M?xico. 3113 records from Butterfly_conservation_2017_12_18. 16333 records from Inventaires faune. 5 records from Laubwald Dreil?ndereck (Aachen/Vaals[NL]). 135567 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 59 records from Suivi botanique et entomologique pour la gestion de la port?e de RTE sur l'emprise de la RNN de Bass?e. 356 records from Inventario herpetofaun?stico del noroeste de Hidalgo. 94 records from WildesMoor bei Schwabstedt. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 8025 records from ZooplanktonBeaufortSeaNOGAP2. 7 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 211 records from Donn?es des naturalistes POHIER et LEFORT provenant de la base de donn?e du SINP ?le-de-France CETTIA. 150 records from CNMA/Colecci?n de Mam?feros de la Estaci?n de Biolog?a Chamela. 1386 records from Aves de fragmentos de Bosque seco en la regi?n del Caribe Colombiano. 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 1 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 16 records from Microzooplankton abundance and biomass at station TT045_26-3. 537 records from ?tude entomologique de la ZSC du Bois de Vaires. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 3564 records from Donn?es rhopaloc?res collect?es par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Donn?es sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 25 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 105 records from Fish Fauna of Berlin. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 942 records from Inventaire des Col?opt?res Longicornes des Antilles fran?aises. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 1750270 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 957 records from D?partement_du_Var_2017_12_18. 48 records from Wildlife Observations Bardon Hill 31.5.09. 68 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 135 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 32 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 27 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Igua?u National Park (Southern Brazil), including a taxonomic key and distribution data. 261 records from Annales de la Soci?t? entomologique de France [1832- ]. 66 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 1333 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 14 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 71633 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 230 records from Inventaire avifaune. 13625670 records from iNaturalist Research-grade Observations. 13 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 28631 records from Donn?es bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d?indicateurs de biodiversit?. 75 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 2 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 29 records from D?ne am Ulvenberg (Darmstadt). 3 records from Donn?es naturalistes d'Emilie WEBER. 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 20 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 30435 records from Mammals housed at MHNG, Geneva. 2 records from Two new ? Asura - like? Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 4249 records from L?yd?s Open Invasive Alien Species Observations. 35 records from Grillh?tte Wettsaasen, Wiese, Hecken. 2461 records from Swiss Psyllid (Hemiptera) Collections - Basel. 154 records from Donn?es du/de la naturaliste VAN DEN BRINK Sylvie provenant de la base de donn?e du SINP ?le-de-France CETTIA. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 15 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 225 records from UWIZM Mantodea. 5 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 1357 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 425 records from donn?es bibliographiques diverses (non araign?es). 9 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atl?ntica, Brazil. 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10066 records from Exp?dition Karubenthos 2012 : inventaire des Mollusques et des Crustac?s de la Guadeloupe. 2 records from New and interesting species of the generaGalumna andPergalumna (Acari, Oribatida, Galumnidae) from the Montagne d?Ambre National Park, Madagascar. 22 records from New records of ant species from Yunnan, China. 22 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 3202 records from Caracterizaci?n biol?gica en la Serran?a de San Lucas 2015. 25 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 186 records from Great Koala Count 2. 1 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 1013 records from Bird specimens of Komatsu City Museum. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 5 records from Donn?es naturalistes de BRULE Herv?. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rond?nia, western Amazonia, Brazil. 5966 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 2 records from Boreonemoral regnskog p? ?stsiden av Lygrespollen. 22 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 6 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 24 records from Liste des oiseaux de BZM Belambo. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 23 records from Donn?es esp?ces - Expertise IPE 123. 50 records from Beetles on polypores at 4 sites in Norway. 14 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 17398 records from NEON Biorepository Invertebrate Bycatch Collection (Archive Pooling). 78 records from Collection Crustacea - ZSRO. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 1547 records from Digitalizaci?n de la Biblioteca de Sonidos Naturales del Museo de Zoolog?a, Facultad de Ciencias, UNAM. 89 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 1 records from Dysaphis (Dysaphis) kadyrovi sp. nov. ? a new aphid species (Hemiptera: Aphididae) from Tajikistan. 1 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 151 records from BIRDRACE Rheinische Wasserrallen. 91 records from Loup 2004 pr?sence r?guli?re communale (r?seau Loup-Lynx ONCFS). 28 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 1 records from Revision of the genus Allometopon Kert?sz (Diptera: Clusiidae). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 60 records from Donn?es naturalistes de David HAPPE. 102 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture ? Paris. 20 records from Riedkanal B?tzingen. 1 records from New record of the genus Baetiella U?no, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 54 records from Aves marinas del atol?n Albuquerque durante la Expedici?n Seaflower 2018 - Proyecto Colombia BIO. 58 records from Donn?es du/de la naturaliste Williamson Thomas provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 8 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 1522270 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunci?n, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crust?ceos). 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 15 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 2 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1361 records from C?digos de barras de la vida en peces y zooplancton de M?xico. 2 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 4 records from Loricifera - SMF. 9 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 479121 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 580 records from Colecci?n Ornitol?gica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Donn?es d'observation opportunistes collect?es durant la campagne de pr?l?vements s?dimentaires SHELL/CREOCEAN en Guyane fran?aise en 2013. Shell Exploration and Production France. 16412 records from Arbeitsgemeinschaft Heuschrecken ?sterreichs. 1109 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 1 records from The identity of Parandra laevis Latreille, 1804 and nomenclatural changes in the Parandrinae (Coleoptera, Cerambycidae). 4 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 14 records from Brown University Herbarium. 26 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 89 records from Donn?es du/de la naturaliste Le baron Gaetan provenant de la base de donn?e du SINP ?le-de-France CETTIA. 689 records from Caracterizaci?n biol?gica de la ventana de biodiversidad Montes de Mar?a, Municipio de Colos?, Sucre, Colombia. 92 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 21 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 695 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 303 records from CNAC/Coleccion Nacional de Acaros. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 622 records from hauterivian_echinoids_of_the_paris_basin. 27 records from Nannofossil abundance of Hole 4-31. 846 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 78 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 64 records from Bats of northeastern Vietnam. 211 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 117 records from Programme de valorisation des zones humides chass?es - volet Amphibiens. 1870 records from Caracterizaci?n de flora, edafofauna ep?gea, anfibios y aves del Complejo de P?ramos Pisba, Boyac?. 32 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedici?n Seaflower 2017 - Proyecto Colombia BIO. 677 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 259 records from Bats of Northern Peninsular Malaysia. 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 5 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 84 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 1646 records from ZUEC-HEM - Cole??o de Hemiptera do Museu de Zoologia da UNICAMP. 310 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 150997 records from UWFC Ichthyology Collection. 6656 records from Auburn University Museum of Natural History Invertebrates. 25 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 58 records from Mam?feros laguna El Tinije. 3575 records from DREAL_PACA_-_N2000_-_Parc_Naturel_R?gional_du_Queyras_2017_12_18. 22 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 558 records from ?rea Ot?n Quimbaya - Densidad poblacional valores objeto de conservaci?n Santuario de Fauna y Flora Ot?n Quimbaya, 2016. 80284 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6621 records from MUST, Insecta. 601464 records from Donn?es ONF faune-flore-fonge. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 13 records from Deutsche Schule Budapest. 1402 records from Regroupement de donn?es rhopaloc?res r?colt?es sur la p?riode de 2010-2015 par Cistude Nature. 2 records from Stenus maculifer CAMERON: eine B?chse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 1 records from University of Tennessee Fungal Herbarium. 26270 records from University of Michigan Museum of Zoology, Division of Mollusks. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX ? Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 1378 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos Tota-Bijagual-Mamapacha. 11 records from Donn?es acquises via le r?seau du Conservatoire botanique national du Bassin parisien. 1213 records from Donn?es opportunistes. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 61505 records from DASSH Data Archive Centre Academic Surveys. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 93 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 2 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 43 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 1 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 396 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 21 records from Exkursion Ebertsheimer/Gr?nst?dter Berg. 208861 records from University of Florida Invertebrate Paleontology. 2 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Donn?es naturalistes de Thibault RAMAGE. 7 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 42 records from Vogelstimmenf?hrung durch den Tiergarten. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 1401 records from Localizaciones sat?lite de un ejemplar ("Lorien") de ?guila azor perdicera (Aquila fasciata Vieillot, 1822) en Arag?n. 106 records from Evaluaci?n de la presencia de 'Marmosa robinsoni' e inventario de mam?feros en el Departamento del Atl?ntico. 16694 records from Inventaire des Eph?m?res de m?tropole (Opie). 307 records from Echinodermata of Montenegro (South Adriatic). 2975 records from Tetr?podos de Uruguay. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 200 records from 2019_nsmk_mm_20200324. 194 records from Donn?es de la naturaliste Giordano Charlotte provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 22 records from Propri?t? r?gionale du Moulin des Marais - Inventaire naturaliste 2015. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 7318 records from University of Kentucky Insect Collection. 51788 records from Atlas des Orthopt?res et Mantides de France m?tropolitaine. 6 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rond?nia, Brazil. 64 records from Donn?es du/de la naturaliste Bourdin Dominique provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 251 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 20612 records from UAM Bird Collection (Arctos). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 81191 records from Dry Tortugas Reef Visual Census 2014. 23 records from uncultured prokaryote Targeted loci environmental. 24 records from Ostracoda abundance of Hole 48-406. 391 records from GEOECOLINK_2017_12_18. 2 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 1206 records from UTEP Herpetology Osteology (Arctos). 1768 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 16 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 135998 records from The Scottish Squirrel Database. 95 records from BIRDRACE OAG Neuwerk. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 3 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 35 records from Selz (Ingelheim am Rhein). 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 387 records from Distribuci?n espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, M?xico. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 1 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 14 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 548 records from FBIP: Baboon spider distribution records from selected South African museums. 9533 records from Donn?es du naturaliste Tillier Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 71 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 265 records from Donn?es naturalistes de Laurent PONCET. 2300 records from Colecci?n de Oligoquetos Acu?ticos de la UPV/EHU. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 76 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 63 records from Donn?es 2017 de l'Observatoire de la Biodiversit? des For?ts. 10787 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 60 records from Knechtweide (Kohlfurth). 2525 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 85 records from MCP-Mamiferos - Cole??o de Mam?feros. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 1 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 358 records from Donn?es du Syndicat de la Vall?e de l'Orge Aval (SIVOA). 89 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 23 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 493 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 92 records from Natura 2000 Parc naturel r?gional de Lorraine. 144282 records from Donn?es de l'AFB acquises selon le protocole de p?che compl?te ? un ou plusieurs passages. 1342 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 830 records from Zambian Bat Collections Worldwide. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 141 records from BIRDRACE Punkbirder Helgoland. 277 records from Inventario de gaster?podos terrestres y dulceacu?colas del ?rea focal de Ixcan, Chiapas. 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 2 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 29 records from Nannofossil abundance of Hole 4-29. 1549 records from Helmintos par?sitos de peces del sureste de M?xico. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 28 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 7 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 10 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 121 records from FFH-Gebiet Klosterwasser/Burkau. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 255 records from Donn?es naturalistes de Hubert GUIMIER. 1807 records from Donn?es naturalistes de Herv? BOUYON. 1795 records from Donn?es de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 254 records from Thistle Heads and Ermerged Insects. 76 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 3123 records from Donn?es DREAL Centre-Val de Loire - Faune - 2018. 48476 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 3473 records from RNF - Donn?es du Parc Naturel R?gional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 28 records from Registros de Lepidoblepharis miyatai (Gecko enano) en la costa Caribe Colombiana. 3079 records from Insectes Hym?nopt?res Scollid?s de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 2279 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 3965 records from Weddell Sea macrozoobenthos EASIZ I. 4 records from A new South American species of Banasa St?l (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 1 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 5398 records from Fauna y flora en ?reas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 2086 records from Communaut?_de_communes_Asse_Bl?one_Verdon_2017_12_18. 8 records from Seawater metagenome Targeted loci environmental. 79 records from Waldi-Weiher. 289 records from Gewann Krampf (Heilbronn). 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 43 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingm?hle. 24 records from Donn?es de NICOLAS Vincent (SAPROX). 15 records from Benthic macrofauna abundance of sediment core 13201-002. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 21 records from Pollen profile from Muscotah Marsh B. 18 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 3 records from seawater metagenome Metagenome. 1917 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3767 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1468 records from Colecci?n Regional de Equinodermos de la Peninsula de Yucatan. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 4 records from Determinaci?n de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 56 records from Tejidos colectados en el p?ramo de Pisba, Boyac? - Proyecto Boyac? BIO. 75 records from Birdrace-Bielefinken-Bielefeld. 4054 records from Fish specimens of Toyama Science Museum. 8521 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 121 records from Range table from ostracoda in ODP Hole 143-866B. 47 records from M?ritz-Nationalpark. 14 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 4649 records from Colecci?n Limnol?gica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 143 records from Birdrace-Wannacks_Topti(c)ker-L?beck. 503 records from Museo Provincial de Ciencias Naturales ?Dr. ?ngel Gallardo?, Rosario, Argentina - Colecci?n Peces (MG-ZV-P). 91 records from Wald am Schloss Wittgenstein Bad Laasphe. 11661 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 223 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 6488 records from Donn?es naturalistes de LUPOLI Roland. 68 records from Donn?es du/de la naturaliste JOSSERAND oriane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 698 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 658 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 18 records from Lepidurus arcticus survey Northeast Greenland 2013. 47 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 25 records from Fortalecimiento de la efectividad del manejo y la resiliencia de las ?reas naturales protegidas para proteger la biodiversidad amenazada por el cambio clim?tico. 4792 records from Colecci?n de Reptiles - Museo de Herpetolog?a de la Universidad de Antioquia. 183 records from Relative abundance of ostracods in sediment core Sv09. 910 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 104 records from Ecological study of the plankton in the port of Ostend in 1965. 29 records from R?vision du genre Danuriella Westwood, 1889 (Mantodea). 93036 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 46 records from Atelier Malacologie continentale, 14-15septembre, La Fl?che (Sarthe). CEN Pays de la Loire. 10 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 2 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 61 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Donn?es naturalistes d'Olivier VILLEPOUX. 1786 records from Galathea II, Danish Deep Sea Expedition 1950-52. 11505 records from NCSM Non-molluscan Invertebrates Collection. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 894 records from Sistematizaci?n de la Colecci?n Entomol?gica Forestal del CENID-COMEF. 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 6986 records from Colec??o Entomol?gica do Museu de Hist?ria Natural de Maputo. 39 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 32 records from Craigellachie NNR invertebrate records compiled from SNH files. 17 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 9 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 372 records from Collection Polychaeta - ZSRO. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 99 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 8 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 68 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 7 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 4 records from CEFS_16S_ITS. 17892 records from Biowide Species data. 11 records from Inventaire et regroupement de donn?es Natura 2000. 1198 records from Actualizaci?n de la base de datos de crust?ceos y registro de datos de peces del pac?fico mexicano de la Colecci?n Biol?gica de la Secretar?a de Marina (Peces). 13 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa St?l (Hemiptera: Cercopidae) with description of four new species. 196 records from Schanzenanlage Bergham. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 74 records from Reptiles de la expedici?n al R?o Apaporis - Proyecto Colombia BIO. 22 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 73 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 549 records from Donn?es du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La R?union. 580 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 7 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 59 records from Nannofossil abundance of Hole 37-334. 19 records from Schulgel?nde SGD/Viersen. 1533 records from Donn?es du/de la naturaliste ARNABOLDI Fr?d?ric provenant de la base de donn?e du SINP ?le-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pf?lzerwald. 53 records from Leopard and Weddell seal program 1999/2002. 3609 records from Donn?es naturalistes de S?gol?ne FAUSTEN. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 4 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 8851 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio S?o Francisco basin, southeastern Brazil. 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 8193 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 352 records from Loup 2015 pr?sence occasionnelle communale (r?seau Loup-Lynx ONCFS). 37 records from Lebensraum Flu?/Zwickauer Mulde in Wolkenburg. 13644 records from Collection of Coleoptera. 11 records from Review of the genus Prays H?bner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 37 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 642 records from Ensemble des donn?es Rhopaloc?res. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 15 records from Monitoreo de Murci?lagos en la Etapa de Ejecuci?n de las Obras de Ampliaci?n del EPF Flore?a, Yopal, Casanare. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 85 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 2 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 135 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 2201 records from Soil invertebrates occurrences in European North-East of Russia. 563385 records from Queensland Museum provider for OZCAM. 5 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 6387 records from Donn?es naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Nav?s, and Loneuroides Garc?a Aldrete (Psocodea: ? Psocoptera?: Ptiloneuridae). 984 records from IPAE egg clutches collection (Aves). 75 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology ? Baseline Studies [2009]. 14 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 9115 records from Donn?es d'observations d'orthopt?res en Auvergne, d'Emmanuel Boitier, de 1998 ? 2015.. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 1 records from Range table from benthic foraminifers in ODP Hole 146-889B. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 701 records from Donn?es naturalistes d'Arnaud LE NEV?. 5818 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 3 records from Analyses of the recent components of sediment core PS1219-1. 4 records from Ollieopteryx, a new genus of caddisflies from Madagascar (Trichoptera Dipseudopsidae). 717 records from Redland City Council Citizen Science Portal. 180 records from Caracterizaci?n de algas y comunidad ?ctica de la Isla Cayo Serrana durante la Expedici?n Seaflower 2016 - Proyecto Colombia BIO. 4 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 74 records from Steinbruch Mainz-Weisenau, 3. Jahr. 949 records from Museu Paraense Em?lio Goeldi - Carcinol?gica Collection. 512 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de M?xico, con ?nfasis en las especies del centro de M?xico. 25 records from Pollen profile V and Ausfluss at Krumbach, Germany. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 175775 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 229 records from Queen Charlotte Sound / T?taranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ? Psocoptera?: Lachesillidae) from Colombia. 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75? N section). 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 34 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Par?, Brazil. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 368 records from Donn?es du naturaliste PROVOST romain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 66 records from Wildlife Sightings in the City of Logan. 16133 records from Birds Specimens. 55 records from Schulgel?nde Kranich-Gymnasium (Salzgitter). 92 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : donn?es esp?ces non cibles pi?g?es. 592 records from Caracterizaci?n de Fauna del Banco de H?bitat del Bosque Seco Tropical Antioquia de Terrasos. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 32 records from Fliegenhaupt Marksuhl. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18065 records from DMNS Mammal Collection (Arctos). 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 9 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 310 records from Trondheim urban biodyversity survey. 94 records from Donn?es du/de la naturaliste LUSTRAT Philippe provenant de la base de donn?e du SINP ?le-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 81 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 19 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 660 records from Peces pel?gicos de la Isla Cayo Serrana durante la Expedici?n Seaflower 2016 - Proyecto Colombia BIO. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 200 records from Cole??o de Bryozoa do Museu Nacional - UFRJ. 8784 records from UAM Fish Collection (Arctos). 8808 records from Survey of bumblebees in central Alberta - 2018. 2 records from New data on the taxonomy and distribution of Philippine Ochodaeidae and description of a new species from Central Visayas (Coleoptera: Scarabaeoidea). 70 records from Isotope tracer experiment: meiofauna counts. 25 records from Bird Specimens of The Cattle Museum. 557 records from Corn bunting breeding distribution in Scotland. 900 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from KARSTLANDSCHAFT S?DHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am R?seberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 65 records from Selztal bei Friesenheim. 1457 records from UCM Mammal Collection (Arctos). 18 records from Microzooplankton abundance and biomass at station TT045_19-3. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 2 records from Natural History Museum, Vienna - Herbarium W. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti?aro, Cook Islands, South Pacific. 1940 records from DREAL_PACA_-_N2000_-_Parc_Naturel_R?gional_du_Verdon_2017_12_18. 65 records from Biologia reprodutiva e dieta de Amerotyphlops brongersmianus (Vanzolini, 1976) da Restinga de Jurubatiba, Rio de Janeiro, Brasil (Serpentes: Typhlopidae). 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 25 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 859 records from Floral visits on plants, InsectScale 2008. 52 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 2509 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 43 records from Frohlinder M?hlenbach (Dortmund-Kirchlinde). 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 29 records from Donn?es esp?ces - Expertise IPE 70. 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3561 records from Biogeography of near-shore reef fishes in northern New Zealand. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 17 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 11 records from The InBIO Barcoding Initiative Database: A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann, 1870 (Lepidoptera, Depressariidae). 87 records from Steinbruch Mainz-Weisenau, 2. Jahr. 2172 records from ConDidact Citizen Science Surveys - Snails 2006. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 105 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 28 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 30 records from Schulgel?nde (Wetter). 88 records from Deponie Klausdorf. 712 records from Earthworm Research Group (UCLan) Earthworm Records (UK). 16 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 2387 records from Establecimiento de un ?rea protegida en el Alto y Bajo Calima, ?rea clave de biodiversidad en el Valle del Cauca, Colombia. 14391 records from Enqu?te Lucane. 421 records from Erlengraben/Lipp-Tal (?stringen). 1986 records from Observations de Col?opt?res saproxyliques de Fr?d?ric LACOSTE. 4923 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 378 records from Exp?dition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1484 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality ? Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2394 records from BioGIS - Reptiles - HUJ collections. 1 records from Analyses of the recent components of sediment core PS1222-1. 271 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5154 records from Fishes in the Argentine Sea from 1967 to the present time. 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 210 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 828 records from Donn?es de la structure SNPN - Soci?t? Nationale de Protection de la nature provenant de la base de donn?e du SINP ?le-de-France CETTIA. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 124 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 124 records from Donn?es du/de la naturaliste jourdan christian provenant de la base de donn?e du SINP ?le-de-France CETTIA. 141 records from Revision of the spider genus Hoplopholcus Kulczy?ski (Araneae, Pholcidae). 1771 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 529 records from Colecci?n de Referencia de Macroinvertebrados Bent?nicos del Museo de Ciencias de la Universidad El Bosque. 163 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 10 records from Ostracoda abundance of Hole 32-306. 26 records from Proyecto interno ejecutado por la CONABIO: Sistema de informaci?n sobre Bosque Mes?filo de Monta?a de M?xico para apoyo en programas de restauraci?n (Fase 1). 3 records from New species of karst-dwelling Pselaphinae from southwestern China (Coleoptera: Staphylinidae). 95948 records from Butterflies of Ireland. 3 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 17 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 66002 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27086 records from Formidabel; Belgian Ants Database. 43 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 487 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 70 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 71657 records from CAS Invertebrate Zoology (IZ). 19 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 41 records from Etude d'impact projet d?ouverture de carri?re ? Vaudoy-en-Brie. 55 records from Macroinvertebrados bent?nicos de playas de arena (Monte Hermoso-Pehuen C?, Buenos Aires, Argentina). 8 records from See lilies of the genus Bathy
Keywords: GBIF; biodiversity; species occurrences